Odpowiedzi

2010-03-25T20:23:49+01:00
X-wiek ojca
y-wiek syna
x+y=47
x=47-y

6 lat temu
x-6=6*(y-6)
x-6=6y-36
podstawiamy pod x
47-y-6=6y-36
47-6+36=6y+y
77=7y
y=77:7
y=11-wiek syna

x+y=47
x+11=47
x=47-11
x=36-wiek ojca

6lat temu syn miał 5 lat ,a ojciec 30 -czyli był 6 razy starszy od syna
odp.obecnie ojciec ma 36 lat ,a syn 11
2010-03-25T20:27:05+01:00
» x-wiek ojca
» y-wiek syna

x+y=47
x=47-y

» 6 lat temu
x-6=6*(y-6)
x-6=6y-36
» podstawiamy pod x
47-y-6=6y-36
47-6+36=6y+y
77=7y
y=77:7
y=11-wiek syna

x+y=47
x+11=47
x=47-11
x=36-wiek ojca